Filipperbrevet 3,2-11 og det “radikalt” ny Paulusperspektiv: (eller “Paul Within Judaism”) - Mortensen, Jacob Palle Bliddal (Dansk Teologisk Tidsskrift, 2019)
In this article, I explain the main concepts and positions within the so-called radical new perspective on Paul. I also turn to Philippians 3:2-11 in order to apply “radical” insights to Philippians. Even though radical scholars have not yet produced a complete interpretation of Philippians, several among them have turned to Philippians 3-passage in order to cope with Paul’s apparent vilification of Jews as dogs and his description of his “former” life in Judaism. The radical insights, which flow from these approaches, may not provide a completely new understanding of the letter to the Philippians, but they do compel us to rethink certain traditional perceptions of the Philippian situation and Paul’s self-understanding.